Radiological articular involvement in the dominant hand in rheumatoid arthritis. Issue 5 (October 1980) - Owsianik, W D; Kundi, A; Whitehead, J N; Kraag, G R; Goldsmith, C
Abstract : Scoring the severity of joint involvement in the x-rays of hands of patients with rheumatoid arthritis showed significantly greater joint destruction in the dominant hand. The difference was seen in all the joints, and especially in the wrists, but with the exception of the metacarpophalangeal joint of the thumb. The grip strength was not, however, different in the 2 hands.